PENGARUH TINGKAT PERPUTARAN PIUTANG TERHADAP LIKUIDITAS KOPERASI SYARIAH BINA HUSADA DINAS KESEHATAN KABUPATEN BREBES - Sri Ratih Handayani (Jurnal Strategik, 2019)
This study takes the title "The Influence of Receivable Turnover Rate on Liquidity of Koperasi Syariah Bina Husada Brebes District Health Office". The objectives to be achieved in this study are: 1. To know the level of receivable turnover of Koperasi Syariah Bina Husada Brebes District Health Office. 2. To find out the liquidity level of the Koperasi Syariah Bina Husada in the Brebes District Health Office 3. To determine the effect of the level of accounts receivable turnover on the liquidity of the Koperasi Syariah Bina Husada in the Brebes District Health Office. This type of research is classified as associative research, which is a study that aims to determine the effect of X independent variable and dependent variable Y and how closely the relationship has influence on the Koperasi Syariah Bina Husada in the Brebes District Health Office. While the data collection method used is observation, namely by way of research directly on cooperatives. Documentation is by collecting information that can be obtained through facts stored in the form of letters, diaries, photo archives, results of meetings, journal activities and so on. Interviews are techniques for collecting data by interviewing directly to find out the latest cooperative developments directly. In testing the hypothesis used t test and F test. The results of the study show that at the level of liquidity from the data from 2013 to 2017 using the current ratio has been efficient even though several years have decreased. Regarding accounts receivable turnover from 2013 - 2017 most experienced an increase in receivable turnover. But after testing through simple regression analysis, t test, f test, and coefficient of determination, the results have been carried out about the level of accounts receivable turnover (X) on liquidity (Y), information can be obtained that the receivable turnover variable does not have a significant effect on liquidity . Keywords: Liquidity Ratio, Cash Ratio, Receivable Turnover